Broadscale postseismic gravity change following the 2011 Tohoku‐Oki earthquake and implication for deformation by viscoelastic relaxation and afterslip. Issue 16 (18th August 2014) - Han, Shin‐Chan; Sauber, Jeanne; Pollitz, Fred
Abstract The analysis of GRACE gravity data revealed postseismic gravity increase by 6 μGal over a 500 km scale within a couple of years after the 2011 Tohoku‐Oki earthquake, which is nearly 40–50% of the coseismic gravity change. It originates mostly from changes in the isotropic component corresponding to the Mrr moment tensor element. The exponential decay with rapid change in a year and gradual change afterward is a characteristic temporal pattern. Both viscoelastic relaxation and afterslip models produce reasonable agreement with the GRACE free‐air gravity observation, while their Bouguer gravity patterns and seafloor vertical deformations are distinctly different. The postseismic gravity variation is best modeled by the biviscous relaxation with a transient and steady state viscosity of 1018 and 1019 Pa s, respectively, for the asthenosphere. Our calculated higher‐resolution viscoelastic relaxation model, underlying the partially ruptured elastic lithosphere, yields the localized postseismic subsidence above the hypocenter reported from the GPS‐acoustic seafloor surveying.